Accountability, History, and Archives: Conflicting Priorities or Synthesized Strands? - Dirks, John M. (Archivaria, 2004)
This article explores the relationship between the different notions of archives that emphasize history, memory, and accountability. While they provide different rationales for archives, they should be integrated in support of the archival mission. Included is a discussion on how the recent emphasis on accountability has emerged and on how critics, especially from a postmodernist view, have countered that this emphasis on accountability is too bureaucratic and presentist. It detracts from the long term goals of memory, narrative, and heritage. The paper explores the concept of historical accountability, in which records hold yesterday’s organizations and institutions accountable for their actions today, both in moral and (sometimes) in legal terms. The idea of historical accountability provides one way of synthesizing accountability, history, and memory and new opportunities for archives to be seen as important relevant players in society. RÉSUMÉ Cet article explore la relation entre les différentes notions de l’archivistique qui mettent l’accent sur l’histoire, la mémoire et l’imputabilité; celles-ci, bien qu’elles fournissent des justifications différentes, doivent être intégrées afin d’appuyer la mission archivistique. L’article décrit comment l’insistance a récemment été mise sur l’imputabilité et pourquoi certains penseurs, particulièrement postmodernes, ont critiqué cette tendance comme étant trop bureaucratique et présentiste, portant atteinte aux objectifs à long terme de la mémoire, du récit et du patrimoine. L’auteur présente le concept de l’imputabilité historique, selon laquelle les documents rendent les organisations et les institutions responsables aujourd’hui pour leurs actions d’hier, que ce soit en termes moraux et (quelquefois) légaux. L’idée de l’imputabilité historique permet de faire la synthèse entre l’imputabilité, l’histoire et la mémoire et offre de nouvelles possibilités aux institutions d’archives de jouer un rôle clé dans la société.